The Interface Between Metaphysics and Science - Lawal, Ademola Lukman (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
The interface between metaphysics and science refers to the close-knit relationship between Metaphysics as First Philosophy and science. The first conception of metaphysics by Aristotle makes its appearance after Physics. The issue at hand borders on the lacuna between metaphysics and science, on the first hand, and on the interconnectedness of the metaphysics, and by extension the whole of philosophy, and the sciences of Physics, Chemistry, Biology and Engineering. We must underscore the view that Metaphysics investigates into the ground and foundation of all regularities and irregularities in nature. It is the first philosophy and the first science. We shall, therefore, probe into the development of modern science from classical antiquity and state the mistake of rejecting metaphysics by the logical positivists as a fundamental injury to science. Our attempt to recover and rediscover the metaphysical foundations of science shall reestablish an enabling interface between metaphysics and science. Our discussion shall first be on metaphysics as the first philosophy and the first science. After examining how science has dovetailed from metaphysics, we would reestablish the interface between metaphysics and science.